Performance of bottom ash treated peat soil in improving shear strength - Muhammad Narun Faiz, Mohd Shukri (2018)
The aim of this study is to improve the shear strength of peat soil stabilized by addition of Bottom ash and mixture of Ordinary Portland Cement. An understanding of the stabilized soil properties is the most importance for the design stabilization of settlement or foundation in peat land for building construction. Some conventional laboratory and field experiments were done to determine the relationship between engineering properties of peat soil and undrained shear strength, and to determine the relationship between bottom ash and unconfined compressive strength of improved peat soil. To achieve such purpose, the study examined the effect of bottom ash as stabilizer to increase the shear strength of peat soil after specific period of curing with different proportion amount of bottom ash (5%, 10%, 15% and 20%). The stabilized peat specimens were tested using unconfined compressive test, Atterberg limit, hydrometer, organic content, fiber content, sieve analysis and permeability test. Significant evidence on the positive effects of the admixture at stabilizing peat soil was discovered from laboratory testing investigation of the study. Result from the investigation indicated that addition of the admixture was able to increase unconfined compressive strength and reduce compression of peat soil as compared to those of untreated peat.